A framework integrating interval-valued hesitant fuzzy DEMATEL method to capture and evaluate co-creative value propositions for smart PSS. (1st April 2019) - Liu, Zhiwen; Ming, Xinguo; Song, Wenyan
Abstract: Through analysing evolution of smart PSS, it is a challenge to capture and evaluate co-creative value propositions (CVPs) for smart PSS. This study thus proposes a framework integrating IVHF-DEMATEL method enhanced by an operator of AVL (average vector-length) on CVPs. Given that smart PSS involves multi-stakeholders and its value is co-created, stakeholder types are proposed to define stakeholder value flow network (SVFN). Based on quality characteristics of smart PSS's core elements, dimensions and criterions of CVPs are courageously proposed to align specific CVPs captured from a SVFN. Since different knowledges and skills of experts, their weights are assigned by the operator of intuitionistic fuzzy number. Compared to other techniques handling uncertainty of expert judgement, IVHF element is more powerful in term of hesitancy. To evaluate the interdependent CVPs, IVHF-DEMATEL method is employed to derive the total-relation of CVPs. Moreover, an operator of AVL is firstly proposed to prioritize the CVPs, also is feasible and simpler than multiple operators of modified-CFCS. Furthermore, influence-dependence (I-D) map with cut-offs of hesitant interval and interval value is utilized to give much richer interpretations on evaluation results. Finally, an illustrative case of smart fridge-service system is demonstrated to justify this proposal methodological framework. Highlights: A roadmap on evolution from traditional PSS towards smart PSS is presented. A new topic on co-creative value propositions (CVPs) of smart PSS is put forward. A series of criteria of CVPs dimensions based on quality attributes is identified. A framework integrating the enhanced IVHF-DEMATEL approach is proposed. An influence-dependence map with hesitant fuzzy interval cut-off points is drawn.